Immunohistochemical Detection of Viral Etiopathogenesis in Lambs and Goat Kids with Neonatal Diarrhea - Ozmen, Ozlem; Haligur, Mehmet; Aydogan, Ahmet; Demir, Necdet (Acta Scientiae Veterinariae, 2018)
Background: Neonatal enteritis is an important disease that causes deaths of animals before 3 weeks of age, and results in significant economic losses. Viral agents can predispose the young animals to secondary infections in the gastrointestinal tract, especially in lambs and goat kids younger than 21 days. Although the neonatal diarrhea is common in calves, there is still little knowledge about pathology, pathogenesis and immunohistochemical localization of viral agents that cause neonatal enteritis in lambs and goat kids. In this study, we carried out investigations with the aim of detecting adenovirus, rotavirus, coronavirus and herpes virus in the guts of goat kids and lambs with viral enteritis. Materials, Methods & Results: Adenovirus, rotavirus, coronavirus and herpes virus antisera were applied to paraffin-embedded intestinal tissue from neonatal lambs and kids that had died from enteritis. In addition, viral agents in the gut cells were detected and evaluated by electron microscopy. The study material consisted of 15 lambs and 15 goat kids that were presented for diagnosis. Viral agents were detected by immunohistochemically in 20 out of 30 animals. Rotavirus was diagnosed in 10 animals, adenovirus in five, herpes virus in three and coronavirus in two animals; and these results were supported by the electron microscopy. This study showed that viral agents play an important role in neonatal enteritis in lambs and kids. Discussion: Bacteria, viruses and protozoa may have a role in the etiology of neonatal enteritis and identifying the etiological agents is not always possible without laboratory studies. In addition, the immune system of the animal and environmental factors are important factors for to occurrence of the disease. The ages of the animals in present study varied between 1 and 21 days, but susceptibility to infection was most commonly observed between the ages of 1 and 12 days, and the infected animals immediately died after the appearance of clinical symptoms during this period. The most common clinical symptoms were fever, depression, dehydration, tenesmus, abdominal swelling and loss of appetite. Histopathological examinations revealed mild to severe lesions in the gut samples including hyperemia of vessels, submucosal edema, desquamation, erosion and ulcers of the epithelial layer of the gut, and inflammatory cell infiltration in the submucosa. Enlargement of mucus-secreting cells was most commonly observed. These results are common in neonatal enteritis and an agreement with previous studies and classical knowledge about clinical and pathological findings in this study. The agents of neonatal diarrhea most often isolated in calves are rotavirus, coronavirus, Cryptosporidium and enterotoxigenic Escherichia coli. A diagnosis of viral agents can be made by immunohistochemical examination of tissue fixed in formalin. This study revealed that the most common viral agents in lambs and goat kids neonatal diarrhea was rotavirus. In this study, protozoal and bacterial contamination was also observed. Our current study also showed that coronavirus is not an important etiological factor, compared with other viral causes of diarrhea in small ruminants. However, according to a previous study by our group, its incidence has increased and may be an important viral agent in neonatal enteritis in the future. This study showed that viral etiology was very important to occurring of neonatal diarrhea, practitioners must be taken into consideration when meet this problem. One of the most important prophylactic measurements may be vaccination pregnant sheep or goat for passive immunity of offspring.